Use of preparations of estrogen action in gynecology and obstetrics - Guerrero, Carlos (2015)
An analysis is made about difference between follicular hormone and estrogens, as well as about their physiologic actions: 1.-stimulant action on vaginal mucosa, endocervical glands and endometrium. 2.-inhibitory action on the hypophysis. 3.-complementary stimulant action on the muscular uterine fibres and mammary glands. An analysis is made about their different uses and indications either in functional alterations and illness. Finally, it is said the kind of hormonal product to be used according with the therapeutic action required.